ANALISIS KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA DENPASAR - Yana, Anak Agung Gde Agung; Sutarja, I Nyoman; Ambarawangi, Putu Lissa (JURNAL SPEKTRAN; Vol 8 No 1 (2020): VOL. 8, NO. 1, JANUARI 2020, 2020)
The Denpasar One-Stop Integrated Service and Investment Service of Denpasar city often hears public complaints about the quality of Building Construction Permit, both regarding requirements that are deemed unclear, late issuance of permits, and facilities and infrastructure considered inadequate. The purpose of this study is to determine the quality of Building Construction Permit services and find out the indicators that are priorities for improving service quality so that efforts can be sought to improve the quality of Building Construction Permit services. Data collection was conducted by questionnaire survey of 95 respondents with 26 questions. This study uses Servqual analysis and Importance Performance Analysis (IPA). Based on the results of Servqual analysis, it was found that public satisfaction with Building Construction Permit service quality was classified as dissatisfied, both seen from tangibles, reliability, responsiveness, assurance, and emphaty variables. Of the 26 indicators that require quality improvement, using the Importance Performance Analysis (IPA) analysis obtained 7 indicators which are the top priorities in improving the quality of Building Construction Permit services. Efforts that can be made are the addition of seats in the waiting room, conduct re-examination of files, socialization of regulations and requirements for IMB, conduct training and counseling for employees, and impose strict sanctions on employees who commits a violation.